Halogenation of the N‐Terminus Tyrosine 10 Promotes Supramolecular Stabilization of the Amyloid‐β Sequence 7–12. Issue 2 (25th February 2020) - Maiolo, Daniele; Pizzi, Andrea; Gori, Alessandro; Gazzera, Lara; Demitri, Nicola; Genoni, Alessandro; Baggi, Fulvio; Moda, Fabio; Terraneo, Giancarlo; Baldelli Bombelli, Francesca; Metrangolo, Pierangelo; Resnati, Giuseppe
Abstract: Here, we demonstrate that introduction of halogen atoms at the tyrosine 10 phenol ring of the DSGYEV sequence derived from the flexible amyloid‐β N ‐terminus, promotes its self‐assembly in the solid state. In particular, we report the crystal structures of two halogen‐modified sequences, which we found to be stabilized in the solid state by halogen‐mediated interactions. The structural study is corroborated by Non‐Covalent Interaction (NCI) analysis. Our results prove that selective halogenation of an amino acid enhances the supramolecular organization of otherwise unstructured biologically‐relevant sequences. This method may develop as a general strategy for stabilizing highly polymorphic peptide regions. Abstract : The power of halogens ! The high‐resolution single crystal X‐ray structures of two halogenated derivatives of the amyloid‐β sequence 7–12 demonstrate the role of halogen‐mediated intermolecular interactions in stabilizing the solid‐state supramolecular organization of this otherwise unstructured biologically‐relevant sequence.